Employing arynes in diels–alder reactions and transition-metal-free multicomponent coupling and arylation reactions - Bhojgude, Sachin Suresh; Bhunia, Anup; Biju, Akkattu T. (Accounts of Chemical Research, 2016)
Conspectus <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Arynes are highly reactive intermediates having several applications in organic synthesis for the construction of various ortho-disubstituted arenes. Traditionally, arynes are generated in solution from haloarenes under strongly basic conditions. However, the scopes of many of the aryne reactions are limited because of the harsh conditions used for their generation. The renaissance of interest in aryne chemistry is mainly due to the mild conditions for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. This Account is focused on the Diels–Alder reaction of arynes and their transition-metal-free application in multicomponent couplings as well as arylation reactions. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">The Diels–Alder reaction of arynes is a powerful tool for constructing benzo-fused carbocycles and heterocycles. In 2012, we developed an efficient, broad-scope, and scalable Diels–Alder reaction of pentafulvenes with arynes affording benzonorbornadiene derivatives. Subsequently, we accomplished the Diels–Alder reaction of arynes with dienes such as 1,2-benzoquinones and tropones. Moreover, we uncovered a transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes by the reaction of arynes with styrenes that proceeds via a Diels–Alder/ene-reaction cascade. In addition, we demonstrated the reaction of arynes with indene/benzofurans, which proceeds via a tandem [4 + 2]/[2 + 2] sequence. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Multicomponent coupling (MCC) involving arynes mainly comprises the initial addition of a nucleophile to the aryne followed by interception of the aryl anion intermediate with an electrophile (provided the nucleophilic and electrophilic moieties do not belong to the same molecule). We have disclosed aryne MCCs initiated by N-heterocycles such as (iso)quinoline, pyridine, and aziridines. When (iso)quinoline is used as the nucleophilic trigger and N-substituted isatin as the third component, the reaction affords spirooxazino(iso)quinolines via 1,4-dipolar intermediates. Unexpectedly, using pyridine affords indolin-2-ones, where the reaction proceeds via the pyridylidene intermediate. Additionally, we developed the phosphine-triggered aryne MCCs for the synthesis of functionalized benzooxaphospholes. In another phase of our work, we studied the synthetic utility of CO2 as a one-carbon synthon in aryne MCCs for the synthesis of phthalimides. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Engaging arynes as an aryl source is one of the transition-metal-free methods for arylation reactions. We have demonstrated the N-arylation of aromatic tertiary amines and O-arylation of aliphatic alcohols using arynes. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">It is anticipated that the chemistry of arynes will continue to prosper and will lead to surprising developments for the synthesis of various 1,2-disubstituted arenes of molecular complexity and structural diversity. Future challenges in this area include the utility of arynes in enantioselective transformations and the synthesis and reactions of exotic heterocyclic arynes.
Keywords: 2-Benzoquinones; Cycloaddition; Facile N-arylation; O-arylation; One-Pot; Aldehydes; Benzyne; Amines; Heterocycles; Acids; 1